Gaze on the Day of As-Shura from the Perspective of Islamic History - Aliya Zavira Parinduri (Yayasan Bayt Shufiya Nusantara, 2025)
The day of Ashura, which falls on the 10th of Muharram, has an important significance in Islamic tradition, remembering various religious events such as the rescue of the Prophet Moses and the healing of the Prophet Ayyub. This research aims to explore the spiritual, historical, and social dimensions of Ashura Day and its role in strengthening the faith and solidarity of Muslims. With a qualitative approach and historiography method, this study analyzes primary data from literature studies related to its historical aspects. The findings show that Ashura Day not only commemorates the history of Islam, but also strengthens social ties through cultural traditions, such as the making of Ashura porridge, which promotes harmony in the midst of the diversity of the people.